THE RELATIONSHIP BETWEEN FOOT ARCH AND OCCUPATIONAL FACTORS IN LECTURERS OF HO CHI MINH CITY UNIVERSITY OF EDUCATION (Vietnam Journal of Community Medicine, 2026)
Objectives: This study evaluated the foot health, focusing on the arch index and its relation to teaching hours.Methods: A cross-sectional study with 70 university lecturers which were collected plantar footprint and FADI surveys grouped by annual teaching hours. Foot function was assessed by Foot and Ankle Disability Index (FADI), and self-reported frequency of foot problems. Arch index was classified from static (non-weight-bearing) and dynamic (weight-bearing) footprints.Results: A total of 78.6% of lecturers reported foot problems, mainly in the ankle and heel. Median FADI scores in foot problems domain were lower than counter part. The arch index significantly increased under load (p < 0.001). At rest, about 50% of feet were classified as normal arch, 30% as high arch, and 20% as low arch. Under load, the prevalence of flat feet rose to 50-60%, while high arches decreased to around 10%.Conclusion: Foot problems are highly prevalent among lecturers, especially in the ankle and heel, and are associated with reduced FADI scores. Weight-bearing caused significant arch flattening and increased plantar contact area.
Keywords: Ankles, foot pain, lecturers, foot function, risk factors.